MODIFIKASI MESIN PENGUPAS SABUT KELAPA - Ariantama, Bima; Ansori, Zulfi; Pranata, Ferdi (Politeknik Manufaktur Negeri Bangka Belitung, 2025)
Coconut fruit has various benefits, ranging from its use as a source of food, drink, medicine, to raw materials in the cosmetic industry. Almost all parts of the coconut fruit can be used, such as coconut leaves, wood, coconut water, coconut shells and coconut fiber. Coconut coir is used as a raw material in the manufacture of strong and durable ropes, webbing, brushes, brushes, broom sticks, and fabrics. In the Bangka Belitung Islands, people still use sharpened machetes/machetes and crowbars as tools for peeling coconut coir. The purpose of modifying the coconut coir peeling machine is to reduce the failure rate of stripping coconut coir by prioritizing work safety and speed in stripping coconut coir, therefore we need a coco peeling machine that can achieve the desired goal. At this stage the design process is carried out by applying the VDI 2222 (Verein Deutsche Ingenieuer) method. Modification of the coco peeling machine can peel the coco with the fastest time of 1 minute and the longest time of 2 minute